2008
DOI: 10.1007/s12072-008-9108-8
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of development of entecavir resistance during entecavir treatment for nucleoside-naive chronic hepatitis B

Abstract: Background Entecavir (ETV) is a potent nucleoside analogue against hepatitis B virus (HBV), and emergence of drug resistance is rare in nucleoside-naive patients because development of ETV resistance (ETVr) requires at least three amino acid substitutions in HBV reverse transcriptase. We observed two cases of genotypic ETVr with viral rebound and biochemical breakthrough during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In a Japanese case, the patient received 0.1 mg/day ETV for 52 weeks and developed three resistance substitutions. Suboptimal dosing of ETV may be a possible contributing factor to resistance [7]. Colonno et al [3] reported that the emergence of ETV resistance in nucleoside-naive patients would likely require the emergence of viruses containing at least three resistance substitutions in a very small sub-population of patients who harbor infected cells/cccDNA that simultaneously encode LAM-resistant/ETV-resistant viruses [3,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Japanese case, the patient received 0.1 mg/day ETV for 52 weeks and developed three resistance substitutions. Suboptimal dosing of ETV may be a possible contributing factor to resistance [7]. Colonno et al [3] reported that the emergence of ETV resistance in nucleoside-naive patients would likely require the emergence of viruses containing at least three resistance substitutions in a very small sub-population of patients who harbor infected cells/cccDNA that simultaneously encode LAM-resistant/ETV-resistant viruses [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the American Association for the Study of Liver Diseases (AASLD) guidelines recommend ETV as the first-line antiviral agent for treatment-naive chronic hepatitis B (CHB) patients [6]. However, rare cases of ETV resistance have recently been reported in treatment-naive patients [7]. We also experienced one case of genotypic ETV resistance with viral rebound during ETV treatment of nucleoside-naive patients with CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the results also suggested that NA treatment is the major selecting factor of primary drug-resistant mutations and that NA treatment promotes putative NAr mutations (Li et al, 2012). Moreover, several previous studies showed that primary NAr mutations occur in patients with no history of NA treatment (Han et al, 2009;Kobashi et al, 2009;Pastor et al, 2009). Recently, another paper also reported that HBV resistance mutations were identified in 5 % of treatment-naïve patients by using INNO-LiPA (Fujirebio) line probe analysis (Mirandola et al, 2011).…”
mentioning
confidence: 99%
“…Recently, however, rare cases of ETVr, which developed in nucleoside-naive patients, have been reported (14)(15)(16). We also observed one patient who developed ETVr-associated HBV RT substitutions, followed by virologic and biochemical breakthrough after complete viral suppression in longterm ETV treatment of nucleoside-naive CHB patients.…”
Section: Introductionmentioning
confidence: 54%
“…In that report, ETVr developed in a nucleoside-naive patient with genotype H of HBV, which did not achieve undetectable HBV DNA levels. In another report, ETVr have been emerged in two Japanese nucleoside-naive CHB patients after prolonged therapy and incomplete suppression (15). Finally, in a recent report, the three substitutions associated with ETV and LVD resistance has been developed simultaneously without complete suppression in a nucleoside-naive CHB patient after extended therapy (16).…”
Section: Treatment Of Chb Has Evolved Markedly With the Introduction mentioning
confidence: 95%